PKM Kelompok Nelayan " Raja Tuna" di Kelurahan Wuring, Kecamatan Alok Barat, Kabupaten Sikka - Konstantinus Pati Sanga; Barnabas Pablo P.W Bhokaleba; Cicilia Ayu Wulandari Nuwa; Maria Trappistin Ose Krowin; Theresia Vitriana Manise (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
This community service program was carried out at the Tuna King Joint Business Group in Wuring Village, Sikka Regency, which faced the main problem in the form of low literacy and financial management of fisher households as well as the use of tuna cutting tools that were used and unhygienic, thus causing waste of production products. The purpose of this activity is to improve the financial management ability of fisher families while increasing production efficiency through the application of appropriate technology. The methods used are financial education and coaching which includes financial literacy education, practical training, and ongoing mentoring, as well as the procurement of 13 units of Victorinox Butcher Straight knives as a means of production. Evaluation was carried out using pre-test and post-test to measure the level of understanding of participants. The results of the activity showed a significant increase in financial management understanding, as shown by the increase in the average score of participants from 2.24 in the pre-test to 3.87 in the post-test. Participants also showed improved ability in recording daily transactions, calculating surplus and deficit, as well as planning savings and family investments. In addition, the use of Victorinox Butcher Straight knives results in cleaner and more precise cuts of tuna, reducing waste, and improving product quality and selling value. These findings show that the integration of family financial education with the provision of appropriate technology is effective in strengthening economic capacity and fishermen's welfare in a sustainable manner.